Level Kemampuan Literasi Matematis Pada Buku Tematik Terpadu Untuk Siswa Kelas 6 Tema Selamatkan Makhluk Hidup - palupi sri wijayanti; Ganung Anggraeni (JIKAP PGSD: Jurnal Ilmiah Ilmu Kependidikan, 2020)
This study aims to determine the level of mathematical literacy skills in the integrated thematic book on the theme of saving creatures in grade 6 used by the students. This research approach is descriptive qualitative and the type of research is literature. Primary data sources are integrated thematic books on the theme of saving living beings in grade 6 and secondary data sources are references to support students' mathematical literacy abilities. The data processing technique is done by editing, organizing, and drawing conclusions. The data analysis technique used is the content analysis which aims to provide systematic and printed written information and discussion. The results showed that the mathematics literacy skills of students in grade 6 SD were at level one, two, and three. Level three explains that students can carry out procedures clearly, including procedures that require sequential decisions.